Examination and Assessment Principles: Integrating Assessment with Teaching-Learning Processes - Bhatia, Ravi P. (JOURNAL OF INDIAN EDUCATION, 2009)
An analysis is made about the well-known drawbacks and inadequacies of the present examination system in India in terms of the poor quality of questions, lack of transparency and its inability to cater to the needs of the modern society that requires skilled manpower. There are also administrative difficulties although some of them like cheating in examinations and late declaration of results have to a considerable extent being successfully addressed. We underline the limitation of the present examination system which is mainly used for certifying purposes and which is integrated only to a limited extent with the larger teaching-learning system. We point out that a proper assessment system similar to the one that prevails in U.K. and elsewhere, not only fulfils this basic need but also helps the teachinglearning aspects both of students and faculty. This is done by a proper understanding of the objectives and principles of assessment, by aligning the assessment with the curriculum and by giving periodic feedback to students. A brief discussion about the various types of assessments and their objectives, and how they are able to improve the educational system and generate requisite skills is made. The need for proper infrastructure and qualified teachers who enjoy trust and support systems is also stressed.